H3K9 methyltransferases and demethylases control lung tumor-propagating cells and lung cancer progression. Issue 1 (December 2018) - Rowbotham, S.; Li, F.; Dost, A.; Louie, S.; Marsh, B.; Pessina, P.; Anbarasu, C.; Brainson, C.; Tuminello, S.; Lieberman, A.; Ryeom, S.; Schlaeger, T.; et al.
Abstract Epigenetic regulators are attractive anticancer targets, but the promise of therapeutic strategies inhibiting some of these factors has not been proven in vivo or taken into account tumor cell heterogeneity. Here we show that the histone methyltransferase G9a, reported to be a therapeutic target in many cancers, is a suppressor of aggressive lung tumor-propagating cells (TPCs). Inhibition of G9a drives lung adenocarcinoma cells towards the TPC phenotype by de-repressing genes which regulate the extracellular matrix. Depletion of G9a during tumorigenesis enriches tumors in TPCs and accelerates disease progression metastasis. Depleting histone demethylases represses G9a-regulated genes and TPC phenotypes. Demethylase inhibition impairs lung adenocarcinoma progression in vivo. Therefore, inhibition of G9a is dangerous in certain cancer contexts, and targeting the histone demethylases is a more suitable approach for lung cancer treatment. Understanding cellular context and specific tumor populations is critical when targeting epigenetic regulators in cancer for future therapeutic development. The effects of epigenetic regulators on different tumor cell populations can affect their potential as anticancer targets. In this study, the authors demonstrate that the histone methyltransferase G9a is a suppressor of lung tumor-propagating cells and tumor progression, acting through chromatin modification with MMP10 as one of its targets for metastasis regulation.